Analisis Kinerja Badan Pertanahan Nasional dalam Mewujudkan Program Pendaftaran Tanah Sistematis Lengkap Berdasarkan Peraturan Menteri Agraria dan Tata Ruang Nomor 6 Tahun 2018 di Kabupaten Tapanuli Utara - Alti Laksana Simaremare; Ramsul Nababan (Universitas 17 Agustus 1945, 2024)
This research aims to determine the performance of the North Tapanuli National Land Agency in realizing the Complete Systematic Land Registration program based on the regulations of the Minister of Agaria and Spatial Planning Number 6 of 2018 and to examine the factors that influence the National Land Agency in realizing the Complete Systematic Land Registration program in North Tapanuli Regency. . This research is empirical juridical legal research. The research method used in this research is qualitative using a descriptive approach. Data collection was carried out using primary data and secondary data. Primary data was obtained through interviews, documentation and observation. The data obtained was obtained through books, journals and articles that were relevant to the topic studied. The results of this research show that the performance of the National Land Agency in realizing the Complete Systematic Land Registration program based on Minister of Agrarian and Spatial Planning Regulation Number 6 of 2018 in North Tapanuli Regency has gone well and shown satisfactory results in various performance indicators such as productivity, service quality, responsibility, responsibility, and accountability. The factors that influence the National Land Agency in realizing a complete Land System Registration are, the commitment of the central and regional governments, adequate budget allocation, policies that support legal certainty and technical support and professionalism during implementation. Inhibiting factors in realizing the Complete Systematic Land Registration program are less than optimal community participation, differences and incomplete documents, complexity of customary land ownership, geographical constraints and limited human resources.